2009
DOI: 10.1055/s-2009-1216511
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Chemical Constituents from Seeds of Nigella sativa L. by using HPLC-UV and Identification by LC-ESI-TOF

Abstract: An HPLC method was developed for the simultaneous determination of nine compounds of Nigella sativa L. The separation was achieved within 23 min by using C18 column material, a water-acetonitrile mobile phase, both containing 0.1% acetic acid gradient system and a temperature of 35°C. The method was validated for linearity, repeatability, LOD, and LOQ. The LOD and LOQ of nine compounds were in the range of 0.09-10 and 0.3-25 mg/mL, respectively. The wavelength used for quantification with the diode array detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…HPLC and GC-MS in quantifying the N. sativa seeds extract (Velho et al, 2011;Avula et al, 2010;Lupidi et al, 2010). However, these two common quantifying methods are relatively expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…HPLC and GC-MS in quantifying the N. sativa seeds extract (Velho et al, 2011;Avula et al, 2010;Lupidi et al, 2010). However, these two common quantifying methods are relatively expensive and time consuming.…”
Section: Introductionmentioning
confidence: 99%
“…LC-MS spectral interpretation allowed for the identification of four alkaloids, magnoflorine, nigellidine, dihydronigellidine, and nigelanoid; four saponins, hederagenin, hederageninpentoside, tauroside E, and hederagenin methyl ester; three monoterpenes, thymoquinolglucoside, thymoquinone, and thymoquinolglucuronic acid; one flavonoid, kaempferol; four phenolic acids, vanillic acid, methoxy cinnamic acid, caffeic acid 3-O-glucuronide, and (E)-p-coumaric acid; and three fatty acids, marked by their MS/MS and in negative ionization mode. [M-H-Rha-Pent (308)] − due to loss of rhamnose and pentose sugar, which were suggested as hederageninpentoside (7) and tauroside E (8) (Figure S5), respectively [30][31][32] [29,30]. For compound 4, the ions were observed in the MS/MS spectra with fragment ions at m/z 310.07 [M-H-CH 3 ] − , 282.09 [M-H-CH 3 -CH-CH 3 ] − , and 163.00 [M-H-glucose (162)] − , corresponding to thymoquinolglucoside (Figure S7) [28,32].…”
Section: Qualitative Characterization Of Phytoconstituents In N Sativ...mentioning
confidence: 99%
“…While the molecular ion peak at m/z 117.87, along with the fragment ion 159.90 [M-H-H 2 O] − , allowed for the assignment of compound 11 as methoxy cinnamic acid, based upon the molecular ion peak at m/z 355.3 and the product ions 179.14 [M-H-glucuronic acid (176)] − and 163.15 [M-H-glucuronic acid-H 2 O] − , it was suggested that compound 13 is caffeic acid 3-O-glucuronide (Figure S10). Phenolics commonly form a pseudo-molecular ion [M-H] − corresponding to a deprotonated molecule and a characteristic fragment ion [M-H-44] − related to CO 2 loss from the carboxylic acid group [30,31].…”
Section: Phenolic Acidsmentioning
confidence: 99%
“…A decrease in the thymoquinone content of methanolic extract may be associated with the thermal conversion of this compound, which is favored by high temperature extractions. In the literature, this compound has been classified as a light-and heat-sensitive compound and it has been reported that exposure to light and heat induced the conversion of this compound [26,29]. Time was also shown to have a negative effect on the thymoquinone content of extract throughout the whole studied temperature range.…”
Section: Effects Of Extraction Conditions On Thymoquinone Content Of mentioning
confidence: 99%
“…Solvent/solid extraction was carried out as an overnight process with gentle stirring. Methanol is one of the most commonly used solvents in the literature for the successive extraction of thymoquinone from black cumin seeds [11,16,26,27]. Another point is the solvent/solid ratio being significant on mass transfer taking place during the extraction process, as its higher value provides more effective mass transfer.…”
Section: Extraction Of Thymoquinone Using Conventional Methodsmentioning
confidence: 99%